Pemanfaatan Ekstrak Abu Sekam Padi sebagai Green Inhibitor pada Baja Karbon dalam Media Air Laut Buatan - DEVI EKA SEPTIYANI ARIFIN; Destri Muliastri (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Rice husk ash is a high resources of silica about 20%. Husk ash contains silica as much as 87% - 97%. One of the uses of silica is to control the occurrence of corrosion by adding a green inhibitor from rice husk ash extract. Furthermore, green inhibitors were tested for their content by FTIR. In the next step, a green inhibitor was added to 3.5% NaCl corrosive media with variations of green inhibitor 0%, 1%, 3%, 5%, and 7% and the length of immersion of ST41 steel plate for 7 days for weight loss testing. The next process is the corrosion rate test, weight loss test and morphology test to see the depth of corrosion that occurs on the plate. The results of the FTIR test showed the presence of silica contained in the green inhibitor of rice husk ash extract. The addition of this green inhibitor causes a decrease in the corrosion rate of ST 41 Steel in a 3.5% NaCl solution. In the Potentiodynamic Polarization (PDP) test, the corrosion rate value with the addition of 5% green inhibitor’s decreased from 0,01482 mpy to 0.00319 mpy with an inhibition efficiency value of 78,446%. Changes in the corrosion rate on the morphology of steel that had been soaked for 7 days were characterized by optical microscopy, it was seen that corrosion growth decreased with increasing concentration of green inhibitor.